Antifungal starch-based edible films containing Aloe vera. (November 2017) - Ortega-Toro, Rodrigo; Collazo-Bigliardi, Sofía; Roselló, Josefa; Santamarina, Pilar; Chiralt, Amparo
Abstract: Aloe vera gel, analysed as to its antifungal properties against six fungi causing plant diseases, was found to be most effective against Fusarium oxysporum. It was included in different ratios in starch based films plastiziced with glycerol to obtain antifungal films. These were characterized as to their physical (barrier and optical) and structural properties. Films containing the highest ratio of Aloe vera solids (1:1, with respect to starch) and different glycerol mass ratios with respect to starch (0.15 and 0.25) were analysed as to the water sorption and water plasticization effects, in order to discover the water sensitivity of the films in different RH ambients. Films with 0.15 g glycerol/g starch were more homogenous, with a lower degree of starch crystallization, reduced water vapour permeability and higher gloss and transparency. These films with the highest Aloe vera ratio were effective at controlling fungal decay and weight loss in cherry tomatoes. Graphical abstract: Highlights: Aloe vera gel was effective against Fusarium oxysporum. Aloe vera could be effectively incorporated into starch matrices to obtain coatings. Coatings with Aloe vera were effective at controlling fungal decay in tomatoes.